Guillain Barre’ Syndrome– A post-infectious sequele of COVID-19 in postnatal period & its treatment modality: A case report (Bangladesh Critical Care Journal, 2021)
We present a case of 26 years old lady, who was diagnosed as GBS in her postpartum period after being infected with COVID-19. Initially she had mild sore throat and cough but was diagnosed with COVID-19 after undergoing normal vaginal delivery which was done as a part of routine investigation. Later she developed sudden blurring of vision, severe headache along with quadriparesis, arefexia, slurring of speech with nasal voice. On the basis of this she was diagnosed as a case of GBS clinically and was treated with IVIG. She was taken care under critical care medicine department for a week where she improved clinically but still her qaudriparesis persisted with diminished reflex.Bangladesh Crit Care J September 2021; 9 (2): 109-111